Effect of stocking density on growth and fertility in the ornamental fish, Xiphophorus helleri - James, R; Sampath, K (Indian Journal of Fisheries, 2011)
In order to determine the optimum stocking density, the red swordtail fish, Xiphophorus helleri was reared at different stocking densities (10, 25, 50, 100 and 150 fish/50 l of water) under aerated and non-aerated conditions and studied the survival, growth and reproductive potential. An increase in stocking density reduced the survival, conversion rate and fertility in X. helleri. Significant (P < 0.05) negative correlation was obtained between density versus feeding parameters (feeding rate, conversion rate and conversion efficiency) or gonad weight and fertility under both aerated and non-aerated conditions. The aeration exhibited better responses than non-aeration in all density groups; however, low density groups (10 and 25D) did not show significant (P > 0.05) differences between them. Animals reared in 10D aerated group had released 266 young ones, while those reared in 25, 50, 100 and 150D aerated groups had released 68, 38, 32 and 12 young ones respectively during the experimental period of 154 days. Non-aerated density groups released less number of young ones than aerated groups. Although 25D group showed 100% survival, fish reared in 10D group displayed better feeding parameters, gonad weight and fertility than 25D group, and hence 10 fish/50 l (10D) is considered as optimum density for X. helleri.